Mosby's over-the-counter medicine cabinet medicines - Donjon, Richard P. (St. Louis : Mosby - Year Book, 1997)
A reference guide on over-the-counter medications aimed at meeting the increasing demand among health-conscious consumers for understandable, accessible information on drugs approved for over-the-counter use. Information is supplied on the symptoms, a simplified mechanism of action explaining how the drugs work to relieve symptoms and a list of all over-the-counter products available to relieve symptoms. Additional information is provided on side effects interactions and precautions, use in the elderly and in children and use by pregnant women or nursing mothers.
Acne -- allergies -- asthma -- cold sores - mouth pain -- constipation - diarrhoea -- colds, coughs and flu -- diet aids -- hemorrhoids -- motion sickness -- pain relievers -- skin problems -- sleep aids -- stomach problems -- sunburn - suntan -- women's health needs -- chlidren's health needs -- other health considerations.
Includes index.
Thumb indexed.
Keywords: Drugs, Nonprescription -- Handbooks, manuals, etc; Patent medicines -- Handbooks, manuals, etc; Consumer education